2014
DOI: 10.1016/j.vetpar.2014.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of the wild canid, Cerdocyon thous, with the piroplasmid Rangelia vitalii in Brazil

Abstract: Canine rangeliosis, caused by the piroplasmid protozoon Rangelia vitalii, is currently recognized as a reemerging disease that affects domestic dogs in Brazil. In the present study, piroplasmid infection was searched in wild canids (20 Cerdocyon thous and 4 Lycalopex gymnocercus) in Brazil. Molecular analysis, based on PCR and DNA sequencing of a portion of the 18S rRNA gene, revealed that 30% (6/20) C. thous were infected by R. vitalii. Blood and bone marrow samples from one of the R. vitalii-infected C. thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
0
35
0
3
Order By: Relevance
“…It is easier to view the parasite during fever peaks in blood smears (PESTANA, 1910b;SILVA et al, 2011). It has been shown that the tick Amblyomma aureolatum is the vector responsible for its transmission (SOARES et al, 2014). This tick species also infects wild animals, which are thought to act as reservoirs for R. vitalii.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easier to view the parasite during fever peaks in blood smears (PESTANA, 1910b;SILVA et al, 2011). It has been shown that the tick Amblyomma aureolatum is the vector responsible for its transmission (SOARES et al, 2014). This tick species also infects wild animals, which are thought to act as reservoirs for R. vitalii.…”
Section: Introductionmentioning
confidence: 99%
“…This tick species also infects wild animals, which are thought to act as reservoirs for R. vitalii. Molecular studies have detected R. vitalii in the blood of Cerdocyon thous and Lycalopex gymnocercus (SOARES et al, 2014;QUADROS et al, 2015). Rangelia vitalii-infected dogs are found in rural and urban fringe areas, especially in areas close to forest and wilderness (BRAGA, 1935;LORETTI & BARROS, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, rangeliosis is diagnosed in wild canids using PCR (SOARES et al, 2014) and macroscopic and histological analyses (FREDO et al, 2015). The disease has also been described in other countries of South America, such as Argentina (EIRAS et al, 2014) and Uruguay (SOARES et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two real-time polymerase chain reaction (qPCR) assays have been developed to detect and quantify R. vitalii in the blood of dogs. One uses the 18s RNA gene fragment with SYBR ® Green (PAIM et al, 2016), and the other uses a TaqMan probe (SOARES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several emerging vector-borne pathogens have also been described and may represent a challenge in diagnosis, since clinical signs may be misinterpret (DantasTorres and Otranto, 2016). The piroplasm Rangelia vitalii is etiological agent of canine rangeliosis, and have been described infecting domestic and wild canids in South America (Eiras et al, 2014;Quadros et al, 2015;Soares et al, 2015Soares et al, , 2014, mainly in the South and Southeastern Brazilian states (Gottlieb et al, 2016;Lemos et al, 2017;Malheiros et al, 2016;Quadros et al, 2015;Silveira et al, 2016;Soares et al, 2014Soares et al, , 2011. Canine rangeliosis may cause a variety of clinical signs, such as apathy, intermittent fever, ear's margin bleeding and anemia (França et al, 2014), with an average lethality rate of 33,3% (Soares, 2014).…”
Section: Introductionmentioning
confidence: 99%